SISTEM ORGANISASI SOSIAL DAN TATANAN KEMASYARAKATAN ADAT SUKU BADUY LUAR - Amalia, Siti; Sapriya; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Baduy tribe, located in Banten Province, is one of the traditional communities in Indonesia which has a unique social and community organization system. This research aims to describe in depth the social organization system of the Outer Baduy Tribe, including the organizational structure, the relationship between the Kajaroan in Outer Baduy and the government, as well as the social structure. The main focus covers aspects of social life ranging from marriage, death, to customary sanctions for violations of customary norms. This research approach uses a literature review method by analyzing various literature sources, in the form of books, journal articles and other documents relevant to the study of the social organization of the Baduy Luar community. The research results show that the social organizational structure of the Outer Baduy Tribe is divided into certain levels with roles that are defined by custom. The relationship between the Kajaroan in Outer Baduy and the government is coordinative but still maintains their cultural independence. The social order is regulated by binding customary rules, starting from simple marriage procedures, sacred death ceremonies, to the imposition of customary sanctions for violators of norms as an effort to maintain community harmony. It is hoped that this research can contribute to the wider community's understanding of the rich social and cultural systems of the Baduy Tribe, as well as becoming an important reference for efforts to preserve traditional values ​​in the modern era. Thus, this study provides new insights into the sustainability of local culture amidst changing times.